2016
DOI: 10.3390/su8121175
|View full text |Cite
|
Sign up to set email alerts
|

Foodsheds and City Region Food Systems in Two West African Cities

Abstract: Abstract:In response to changing urban food systems, short supply chains have been advocated to meet urban food needs while building more sustainable urban food systems. Despite an increasing interest in urban food supply and the flows of food from production to consumption, there is a lack of empirical studies and methodologies which systematically analyse the actual proportion and nutritional significance of local and regional food supplied to urban markets. The aim of this empirical study therefore was to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 19 publications
1
55
0
Order By: Relevance
“…Food is connected directly to many dimensions of community sustainability including urban-rural food flow linkages, gender and equity, climate change, water quality and availability, land tenure and economic opportunities including livelihoods, and good health through access to adequate amounts of nutritious and culturally appropriate food (for example, [9,57,58]). Food systems can use these as entry points to develop a holistic understanding of food to include short food supply chains/local food systems to create direct links between growers and eaters so that rural spaces and small/mid-size cities and towns are enabled to foster their own well-being and not be seen to be at the service of larger city centers; agroecology/ecological farming as a transformational solution to cool and feed the world; healthy food to address the double malnutrition burden; and territorial and related bioregional areas as the basis for closed-loop resource flow analyses [59].…”
Section: Understanding the Potential Of A Crfs Approach: The Buildingmentioning
confidence: 99%
“…Food is connected directly to many dimensions of community sustainability including urban-rural food flow linkages, gender and equity, climate change, water quality and availability, land tenure and economic opportunities including livelihoods, and good health through access to adequate amounts of nutritious and culturally appropriate food (for example, [9,57,58]). Food systems can use these as entry points to develop a holistic understanding of food to include short food supply chains/local food systems to create direct links between growers and eaters so that rural spaces and small/mid-size cities and towns are enabled to foster their own well-being and not be seen to be at the service of larger city centers; agroecology/ecological farming as a transformational solution to cool and feed the world; healthy food to address the double malnutrition burden; and territorial and related bioregional areas as the basis for closed-loop resource flow analyses [59].…”
Section: Understanding the Potential Of A Crfs Approach: The Buildingmentioning
confidence: 99%
“…Agri-food researchers agree that urban food systems need to undergo a transition toward sustainability to equally tackle economic, social and ecological obstacles that are caused by a set of intersecting challenges, including climate change, population growth, ecosystem degradation, social inequalities, price volatilities, water scarcity and biodiversity loss [1]. Therefore, lately, increasing attention has been on assessing and planning more sustainable and resilient urban food systems [2][3][4]. In this respect, conceptual links between city planning and urban food system research have also been investigated under the "smart food city" framework [5].…”
Section: Introductionmentioning
confidence: 99%
“…Foodshed maps and related land-based assessments are not only of great help for leaders of local food movements in the United States, but also are widely used internationally [13]. For example, Karg et al [14] found that although food provided within the city region assisted the provision of fresh perishable crops, a larger geographical diversity of foodsheds appeared to strengthen the resilience of local food systems in West Africa. In Europe, drawing upon the concept of urban resilience, foodshed maps were constructed to help policymakers develop the food self-sufficiency scenario in the cities of London, Berlin, Milan and Rotterdam [15].…”
Section: Introductionmentioning
confidence: 99%